(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
In the observation of World Environment Day, the theme chosen for the year, 2016 was “Connecting People to Nature’; for the year of 2017, it was “Biodiversity and Sustainable Tourism‟; and in this year 2018, it is “Celebrating 25 Years of Action for Biodiversity‟. The biodiversity concerning organizations have agreed in a statement that the importance of biodiversity may be focused through the application of various frontiers of the biodiversity. The organizations realize that it is necessary to analyze how the ecotourism justifies its role to bring the people near to nature in an ecosystem of the biosphere. In the socio-ecological aspects, the ecotourism stands as one of the supportive frontiers of biodiversity for utilization of the bio-ecological resources of an area of the planet. The present paper deals with the matters in a collective and integrative structure. J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(1): 1-10